Sphingolipid Synthesis Inhibition by Myriocin Administration Enhances Lipid Consumption and Ameliorates Lipid Response to Myocardial Ischemia Reperfusion Injury - Bonezzi, Fabiola; Piccoli, Marco; Dei Cas, Michele; Paroni, Rita; Mingione, Alessandra; Monasky, Michelle M.; Caretti, Anna; Riganti, Chiara; Ghidoni, Riccardo; Pappone, Carlo; Anastasia, Luigi; Signorelli, Paola (Frontiers in Physiology, 2019)
Myocardial infarct requires prompt thrombolytic therapy or primary percutaneous coronary intervention to limit the extent of necrosis, but reperfusion creates additional damage. Along with reperfusion, a maladaptive remodeling phase can occur, depending on the extent of the damage. This leads to ventricular dilation, mitral valve regurgitation, loss of contractile force, functional impairment, and arrhythmias. A cause of pathological remodeling is related to the reduced ability to recover metabolism homeostasis after infarct, due to inflammation and oxidative stress. Infarcted individuals can exhibit an accumulation of fat in the left ventricle. Increased intra-myocardial fat causes altered electrical activity, fat replacement of fibrous tissue within the scar, and myocardial dysfunction. Reduced lipids turnover and their accumulation is associated with deregulation of peroxisome proliferator activated receptors (PPARs), controlling fatty acids metabolism, energy production, and the anti-inflammatory response. Ceramide is an inflammatory lipotoxin that significantly contributes to myocardial inflammation and failure. The present study aimed to demonstrate that Myriocin, an inhibitor of the biosynthesis of sphingolipids, ameliorates myocardium energy metabolism in the post-infarct phase. LAD coronary transient ligation in mice was performed and Myriocin loaded nanoparticles were injected in the myocardium as a post-conditioning therapy. We previously demonstrated that Myriocin can be effectively used as post-conditioning therapeutic to limit ischemia/reperfusion-induced inflammation, oxidative stress, and infarct size, in a murine model. In this follow-up study, we demonstrate that Myriocin has a critical regulatory role in cardiac remodeling and energy production, by up-regulating the transcriptional factor EB, PPARs nuclear receptors and genes involved in fatty acids metabolism, such as VLDL receptor, Fatp1, CD36, Fabp3, Cpts and mitochondrial FA dehydrogenases. The overall effects are represented by an increased β–oxidation, together with an improved electron transport chain and energy production. The potent immunomodulatory and metabolism regulatory effects of Myriocin elicit the molecule as a promising pharmacological tool for post-conditioning therapy of myocardial ischemia/reperfusion injury.